Mammographic Density and Expression of the Genes Involved in the de novo Cholesterol Biosynthesis: Mammographic density and cholesterol biosynthesis - Coradini, Danila (Archives of Breast Cancer, 2024)
Background: This in silico study investigated the association between the local biosynthesis of cholesterol and mammographic density, the major risk of developing breast cancer, as a function of the three cellular components of breast tissue (epithelium, fatty, and non-fatty stroma). Methods: The study compared the expression of 7 genes (HMGCR, FDPS, FDFT1, GGPS1, SQLE, LSS, and SREBF2) involved in the de novo cholesterol biosynthesis, first, according to the radiological density (dense vs. non-dense breast) and, then, according to the cellular components of breast tissue, regardless the radiological classification. Results: HMGCR, SQLE, and SBREF2 were significantly more expressed in radiologically dense than in non-dense breasts (-1.70 vs. -1.41, P=0.0028; -1.20 vs. -1.11, P=0.0501; -3.63 vs. -3.31 P=0.0003; -0.92 vs. -0.76, P=0.0271, respectively). When the samples were reclassified based on their cellular components as highly fatty and highly non-fatty, HMGCR, SQLE, and SBREF2 were significantly more expressed in highly non-fatty samples (-1.48 vs. -1.94, P<0.0001; -3.39 vs. -4.18, P<0.0001; -0.77 vs. -0.94, P=0.0103, respectively) whereas LSS was overexpressed in high fatty ones (0.28 vs. -0.60, P<0.0001). Besides, while in the highly non-fatty subgroup SREBF2 was positively associated with both HMGCR (r=0.53, P<0.0001) and SQLE (r=0.73, P<0.0001), in the highly fatty subgroup these positive correlations disappeared (SREBF2*HMGCR: r=-0.19, P=0.3026) or substantially decreased (SREBF2*SQLE: r=0.41, P=0.0173). Conclusion: Findings provide a compelling biological explanation for the clinical evidence that women with radiologically dense breasts are at a higher risk of developing cancer compared to those with non-dense breasts because of the prevalence of non-fatty tissue, where the altered expression of genes leading to an increased cholesterol production, can contribute to the transformation of epithelial cells, and support the use of mammographic density as a reliable surrogate marker to identify women who may benefit from a preventive treatment aimed at reducing cholesterol production.